Characterization and correlation analysis of oral NET markers and inflammatory factor levels in patients after orthodontic treatment: a pilot study - Liu, Qian; Wang, Axian; Guo, Donghui; Luo, Houzhuo; Fang, Shishu; Song, Zhixin; Wen, Yi; Jin, Fang (Frontiers in Immunology, 2025)
IntroductionChanges in oral neutrophil number and function may occur in patients after orthodontic treatment, affecting the oral immune microenvironment. However, the specific mechanisms are unclear. In this study, we describe the changes in the levels of neutrophil extracellular traps (NET) markers and inflammatory factors in the gingival crevicular fluid (GCF) and saliva of patients after orthodontic treatment and further explore the correlation between them.Methods68 patients underwent fixed orthodontic treatment in the Department of Orthodontics from January 2021 to June 2023 were selected. GCF and saliva samples were collected from the patients 1 day before orthodontic treatment and 2 h, 24 h, and 1 week after orthodontic treatment to evaluate changes in NET marker and inflammatory factors. The differences in and associations between NET markers and inflammatory cytokine levels in the GCF and saliva of patients were evaluated.ResultsAfter fixed orthodontic treatment, the neutrophil elastase (NE), myeloperoxidase (MPO), citrullinated histone 3 (CitH3), and MPO-DNA in the GCF and saliva of the patients increased gradually, the interleukin (IL)-1β and IL-8 in the GCF increased gradually, and there were significant differences among the different time points (P<0.05). There was a positive correlation between the NE, MPO, CitH3, MPO-DNA, IL-1β and IL-8 in the GCF of patients at 2 hours and 24 hours after orthodontic treatment (P<0.05). There was a significant positive correlation between the GCF and saliva levels of NE, MPO, CitH3, MPO-DNA, IL-1β and IL-8 (P<0.05); however, there was no statistically sex- or age-dependent differences in the NE, MPO, CitH3, MPO-DNA, IL-1β and IL-8 levels in the GCF of orthodontic patients (P>0.05).ConclusionThis study significantly reveals that NET marker levels in the GCF and saliva rapidly change following the initial orthodontic arch wire stress. The inflammation in periodontal tissues induced by orthodontic stress has the potential to trigger oral inflammation via the GCF. These findings are crucial for understanding the oral immune microenvironment changes during orthodontic treatment, providing a theoretical basis for preventing and treating orthodontic - related periodontal complications, thus having important implications for improving orthodontic treatment outcomes.